Cover Feature: Submerging a Biomimetic Metallo‐Receptor in Water for Molecular Recognition: Micellar Incorporation or Water Solubilization? A Case Study (Chem. Eur. J. 68/2018). Issue 68 (26th November 2018) - Collin, Solène; Parrot, Arnaud; Marcelis, Lionel; Brunetti, Emilio; Jabin, Ivan; Bruylants, Gilles; Bartik, Kristin; Reinaud, Olivia
Abstract : A poly(imidazole)–resorcinarene‐based biomimetic receptor performs efficiently for Zn 2+ coordination and anionic guest hosting when encapsulated in micelles or functionalized with water‐solubilising groups. Despite very different microenvironments, binding constants and pH windows are strikingly similar; these results are related to the structuration of the receptor that mimics the active site of metalloenzymes. Micellar incorporation thus represents an easy alternative to difficult synthetic work, which opens many of perspectives for molecular recognition in water. More information can be found in the Full Paper by K. Bartik, O. Reinaud et al. onpage 17964 .